Intracellular β1-Adrenergic Receptors and Organic Cation Transporter 3 Mediate Phospholamban Phosphorylation to Enhance Cardiac Contractility. Issue 2 (13th November 2020) - Wang, Ying; Shi, Qian; Li, Minghui; Zhao, Meimi; Reddy Gopireddy, Raghavender; Teoh, Jian-Peng; Xu, Bing; Zhu, Chaoqun; Ireton, Kyle E.; Srinivasan, Sanghavi; Chen, Shaoliang; Gasser, Paul J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: β1 ARs (β1 -adrenoceptors) exist at intracellular membranes and OCT3 (organic cation transporter 3) mediates norepinephrine entry into cardiomyocytes. However, the functional role of intracellular β1 AR in cardiac contractility remains to be elucidated. Objective: Test localization and function of intracellular β1 AR on cardiac contractility. Methods and Results: Membrane fractionation, super-resolution imaging, proximity ligation, coimmunoprecipitation, and single-molecule pull-down demonstrated a pool of β1 ARs in mouse hearts that were associated with sarco/endoplasmic reticulum Ca 2+ -ATPase at the sarcoplasmic reticulum (SR). Local PKA (protein kinase A) activation was measured using a PKA biosensor targeted at either the plasma membrane (PM) or SR. Compared with wild-type, myocytes lacking OCT3 (OCT3-KO [OCT3 knockout]) responded identically to the membrane-permeant βAR agonist isoproterenol in PKA activation at both PM and SR. The same was true at the PM for membrane-impermeant norepinephrine, but the SR response to norepinephrine was suppressed in OCT3-KO myocytes. This differential effect was recapitulated in phosphorylation of the SR-pump regulator phospholamban. Similarly, OCT3-KO selectively suppressed calcium transients and contraction responses to norepinephrine but not isoproterenol. Furthermore, sotalol, a membrane-impermeant βAR-blocker, suppressed isoproterenol-induced PKA activation at the PM but permitted PKA activation at the SR, phospholamban phosphorylation, and contractility. Moreover, pretreatment with sotalol in OCT3-KO myocytes prevented norepinephrine-induced PKA activation at both PM and the SR and contractility. Conclusions: Functional β1 ARs exists at the SR and is critical for PKA-mediated phosphorylation of phospholamban and cardiac contractility upon catecholamine stimulation. Activation of these intracellular β1 ARs requires catecholamine transport via OCT3.